A journey implementing a knowledge portal: The Dar al-Hikmah Library experience - Mustapa, Nor Hasyimah; Zakaria, Maznah; Marsidi, Suhaila; Zamani, Norfatin Farhanah; Saharudin, Ameerul Ashraf; Nordin, Maisarah (2025)
This article describes how the Dar al-Hikmah Library's knowledge portal was developed through the combined efforts of a select IIUM team and a contracted developer, drawing on insights gained from examining knowledge management portals used in various local academic libraries. The project team significantly improved their proficiency in system development and programming through cooperative work, proactive participation, and technology transfer initiatives. Topics covered in training sessions included user requirements, server configuration, Python, Scrapy, Apache Solr indexing, and more. The architecture of the PHP Laravel-based portal, Solr data storage, and crawling engine achieved efficient data retrieval and storage. Additionally, the team developed 10 knowledge clusters within the portal to enhance information organization and accessibility. The challenge for institutions to make their users aware of their knowledge portals was emphasized, highlighting the need for additional outreach. The iKnow portal project has produced a useful and navigable platform for knowledge management and sharing.